Educational press and its impact on grammar in Chilean school (1893-1899) - Cifuentes Sandoval, Juan Isaías (2026)
In this paper, we have sought to prove the influence of the educational press on the development of grammatical ideas in Chile. Our corpus consists of two journals published at the end of the 19th century: Revista de Instrucción Primaria and Revista del Preceptorado de Atacama. In our analysis, we use the concept of “field” (Bourdieu, 2003) to illustrate how the dissemination of ideas in the specialized press enables the emergence and consolidation of primary school teachers as relevant actors in the local media. We conclude that this process allows for the emergence of new ideas and authorities within the teaching profession, which has an impact on the codification of grammar texts intended for use in schools. Complementarily, we observe that the government benefits from the growing unionization of teachers to disseminate useful ideas in the context of ongoing reforms in the education system.